(untitled) (Bangladesh Journal of Microbiology, 2010)
The investigation was conducted to determine the persistence of maternally derived antibody as well as its influence on vaccination programme against fowl pox infection. A total of 60-day-old chicks divided into four groups such as A, B, C, D. Chicks of Group A and B were used for the detection of persistence of maternally derived antibody which are originated from fowl pox virus-vaccinated and non-vaccinated parent stock respectively. For the detection of antibody level after vaccination with live fowl pox and pigeon pox virus vaccine following two vaccination schedules, chicks of group C and D were subdivided into group C1, C2 and D1, D2 originating from fowl pox virus vaccinated and non-vaccinated parent stock. It is found that maternally derived antibody passed over from the parents to progeny chicks and remains protective level for the chick of group A until day 4 of age and the chicks of group B which are originated from non-vaccinated parent stock remains protective level only at day 1. Chicks of subgroup C2 and D2 produce higher antibody titre, which were boosted at 15 days interval. Frequent out breaks of fowl pox infection in chicks of Bangladesh either from fowl pox virus-vaccinated and non-vaccinated origin may be avoided by vaccination with pigeon pox virus vaccine at day 5 followed by a secondary vaccination with fowl pox virus vaccine at day 21. Keywords: Maternally-derived antibody (MDA); Chicks; Fowl pox (FP); Fowl pox virus (FPV) DOI: http://dx.doi.org/10.3329/bjm.v25i1.4858 Bangladesh J Microbiol, Volume 25, Number 1, June 2008, pp 57-59